Rekonstruksi Sejarah Geologi Berdasarkan Analisis Stratigrafi Daerah Pulau Beringin dan Sekitarnya, Kabupaten Lahat, Sumatera Selatan - Muhammad Aghil Ikhwanulsyah; Yogie Zulkurnia Rochmana (OPHIOLITE: Jurnal Geologi Terapan, 2025)
This study was conducted in Pulau Beringin Village, Lahat Regency, South Sumatra, to reconstruct geological conditions and understand the chronology of sedimentation through stratigraphic analysis. The methods employed include field observations and laboratory-based stratigraphic interpretation. The stratigraphy of the study area, arranged from oldest to youngest, begins with the Saling Formation (KJs), dated to the Late Jurassic–Early Cretaceous, formed by the collision between the Woyla Arc and the West Sumatra Block, resulting in andesitic rocks deposited in a terrestrial setting. It is overlain by the Kikim Formation (Tpok), Paleocene–Oligocene in age, comprising andesitic breccia fragments within a braided fluvial environment. A transgressive phase deposited the Gumai Formation (Tmg) during the Early–Middle Miocene, characterized by carbonate-rich sandstone and shale in a delta front setting. Microfossil analysis confirms its relative age as Middle Miocene. The regressive phase led to the deposition of the Air Benakat Formation (Tma) during the Middle–Late Miocene in a lower delta plain environment, with sandstone and claystone lithologies. The Muara Enim Formation (Tmpm), dated to the Late Miocene–Pliocene, was deposited in an upper delta plain setting, consisting of tuffaceous sandstone and claystone. Finally, the Kasai Formation (Qtk), of Pliocene–Pleistocene age, was deposited in a fluvial environment and comprises conglomeratic sandstone and claystone. The overall depositional sequence was initially driven by tectonic activity, followed by transgressive and regressive cycles.